2011
DOI: 10.5550/sgia.110702.en.177p
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training in Students With Diabetes: The Role Pe Teacher at School

Abstract: SAŽETAKDiabetes je bolest poremećenog metabolizma glukoze i može se podijeliti u dvije kategorije: dijabetes tipa 1 (DMT1), koji je češći u djece, i dijabetesa tipa 2 (DMT2). Fizička aktivnost je pokazalo da ima raznovrsne pozitivne efekte na dijabetičare i zato se preporučuje i učenicima dijabetičarima. Rad nastavnika fizičkog vaspitanja u grčkim javnim školama nailazi na prepreke zbog nedostatka zvaničnih obrazovnih seminara, potrebnih objekata i informisanosti društva kao i pojave školske fobije i sigmatiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
3
0
0
Order By: Relevance
“…Also, the presence of a well-prepared health care support system increased trust in a provider’s tailored advice and engagement in regular daily HE [ 151 , 152 ] and PA [ 2 , 153 , 154 ]. Our results indicated that exclusion from school activities has aggravated the emotional and social impact of diabetes, which confirms earlier results [ 155 , 156 ]. The International Society for Pediatric and Adolescent Diabetes (ISPAD) holds the position that adolescents must be able to manage their diabetes in the school setting without being excluded or discriminated [ 157 ].…”
Section: Discussionsupporting
confidence: 92%
“…Also, the presence of a well-prepared health care support system increased trust in a provider’s tailored advice and engagement in regular daily HE [ 151 , 152 ] and PA [ 2 , 153 , 154 ]. Our results indicated that exclusion from school activities has aggravated the emotional and social impact of diabetes, which confirms earlier results [ 155 , 156 ]. The International Society for Pediatric and Adolescent Diabetes (ISPAD) holds the position that adolescents must be able to manage their diabetes in the school setting without being excluded or discriminated [ 157 ].…”
Section: Discussionsupporting
confidence: 92%
“…Also, the presence of a well-prepared health care support system increased trust in a provider's tailored advice and engagement in regular daily HE [151,152] and PA [2,153,154]. Our results indicated that exclusion from school activities has aggravated the emotional and social impact of diabetes, which confirms earlier results [155,156]. The International Society for Pediatric and Adolescent Diabetes (ISPAD) holds the position that adolescents must be able to manage their diabetes in the school setting without being excluded or discriminated [157].…”
Section: Plos Onesupporting
confidence: 87%
“…Also, the presence of a well-prepared health care support system increased trust in a provider's tailored advice and engagement in regular daily HE [151,152] and PA [2,153,154]. Our results indicated that exclusion from school activities has aggravated the emotional and social impact of diabetes, which confirms earlier results [155,156]. The International Society for Pediatric and Adolescent Diabetes (ISPAD) holds the position that adolescents must be able to manage their diabetes in the school setting without being excluded or discriminated [157].…”
supporting
confidence: 87%